DESIGN OF FRICTION COEFFICIENT TEST EQUIPMENT FOR RAILWAY COMPOSITE BRAKE BLOCK - Nandayouwan, Rizkiandeva
Along with the composite brake block that have started to be used in Indonesia, Badan Standardisasi Nasional (BSN) is designing the SNI requirements of composite brake block for railway facilities to ensure the fulfillment of a braking system that meets all requirements before the brake operate. However, there is no lab in Indonesia that has test equipment regarding to the friction coefficient of composite brake block for railway which is an obstacle. The stages of working on this project begin with gathering information related to the existing friction coefficient test equipment followed by determining the DR&O. Then, brainstorming related to the design concept was carried out followed by 3D modeling of the test equipment with software SolidWorks. Furthermore, the maximum stress calculation for critical components is carried out using software Ansys accompanied by manual calculations using existing theory as validation. Based on the calculation according to the design criteria, the required motor power is 334 kW. Then, the required braking force is 4.99 kN so that the required hydraulic force is 25 kN. Furthermore, with the selection of the type of belt that has been done, 7 belts with power of 60.62 kW per belt are needed.